Nanoparticles alter the nature and strength of intraploidy and interploidy interactions in plants - Elizabeth A. Esser; Jiaqi Tan; Na Wei (Scientific Reports)
Abstract Engineered nanoparticles have profound impacts on organisms, yet there is limited understanding of how nanoparticle exposure shapes species interactions that are key to natural community dynamics. By growing plants of the same (intraploidy) and different ploidy levels (interploidy) of Fragaria in axenic microcosms, we examined the influence of nanoparticles on species interactions in polyploid and diploid plants. Under copper oxide (CuO) nanoparticle exposure, polyploids experienced reduced competition and a shift towards facilitation, when growing with both polyploids (the effect of polyploids on polyploids measured by the relative interaction index, RII8x,8x ) and diploids (the effect of diploids on polyploids, RII8x,2x ). This reduction in competitive interactions in polyploids, in line with the stress gradient hypothesis, was primarily driven by nanoscale effects. In contrast, the strength of competitive interactions (RII8x,8× and RII8x,2x ) increased under CuO bulk particles compared to control conditions. Different from polyploids, diploids experienced neutral interactions (RII2x,2x and RII2x,8x ) under both nanoparticles and bulk particles. These findings highlight ploidy-specific interaction dynamics and the need to consider species interactions when predicting organismal responses to nanoparticle pollution in ecological communities, providing critical insights for conservation strategies and sustainable nanotechnology applications.